PSYCHOEDUCATION PADA KELUARGA DALAM MENCEGAH KEKAMBUHAN PASIEN DENGAN GANGGUAN JIWA (LITERATUR REVIEW) - Riko Sandra Putra; Murtiningsih (LPPM STIKes Mitra Adiguna, 2024)
In general, mental disorders are caused by psychological pressure, both internal and external. One of the causes is family and community ignorance of this mental disorder. To seek literacy about psychoeducation in families in preventing relapse in patients with mental disorders. The search for articles in this systematic review used five databases including: Cochrane, Scopus, Pubmed, Embase and manual search. Based on the results of literature searches through 5 databases, 24,798 articles were obtained that matched these keywords. The search results that have been obtained are then entered into the Mendeley reference manager desktop application to identify the level of relevance to the current study. The first screening process was carried out by removing duplicate articles (n=228), then 24,570 articles were screened based on suitability of the topic in the title and abstract. Articles that did not meet the sample criteria were excluded from the study (n=24,560), leaving 10 articles included in this study. Psychoeducation in the family is very effective in preventing relapse in patients with mental disorders.